2021
DOI: 10.1186/s13045-021-01104-3
|View full text |Cite
|
Sign up to set email alerts
|

The biogenesis and biological function of PIWI-interacting RNA in cancer

Abstract: Small non-coding RNAs (ncRNAs) are vital regulators of biological activities, and aberrant levels of small ncRNAs are commonly found in precancerous lesions and cancer. PIWI-interacting RNAs (piRNAs) are a novel type of small ncRNA initially discovered in germ cells that have a specific length (24–31 nucleotides), bind to PIWI proteins, and show 2′-O-methyl modification at the 3′-end. Numerous studies have revealed that piRNAs can play important roles in tumorigenesis via multiple biological regulatory mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 156 publications
(179 reference statements)
0
34
0
Order By: Relevance
“…The mature piRNA combined with PIWI can direct its complex to the transposon target of the target transcript in the nucleus and mobilize the silencing mechanism to organize the expression of transposable elements to maintain the integrity of the genome ( 24 ). To date, piRNAs have been shown to be involved in transposon silencing, epigenetic regulation, gene and protein regulation, genome rearrangement, spermatogenesis and germ cell maintenance ( 24 , 25 ). Small nucleolar molecule RNA (snoRNA) is a kind of short stranded noncoding RNA related to the chemical modification of ribosomal RNA (rRNA) ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mature piRNA combined with PIWI can direct its complex to the transposon target of the target transcript in the nucleus and mobilize the silencing mechanism to organize the expression of transposable elements to maintain the integrity of the genome ( 24 ). To date, piRNAs have been shown to be involved in transposon silencing, epigenetic regulation, gene and protein regulation, genome rearrangement, spermatogenesis and germ cell maintenance ( 24 , 25 ). Small nucleolar molecule RNA (snoRNA) is a kind of short stranded noncoding RNA related to the chemical modification of ribosomal RNA (rRNA) ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…P-element-induced wimpy testis (Piwi) interacting RNAs (piRNAs) are a novel class of less-studied small ncRNAs originally found in germ cells, which play critical roles in the differentiation and maintenance of germ cells ( Yamashiro and Siomi, 2018 ). piRNAs are 24–31 nucleotides in length and exhibit 2′- O -methyl modifications at the 3′ terminus ( Chen et al., 2021b ). Unlike miRNAs and siRNAs, piRNAs are slightly longer and are generated from single-stranded precursors that do not involve Dicer or the formation of secondary structures ( Lin et al., 2021 ).…”
Section: Mechanisms Of the Ncrna-mediated Regulation Of Osteogenic Si...mentioning
confidence: 99%
“…Unlike miRNAs and siRNAs, piRNAs are slightly longer and are generated from single-stranded precursors that do not involve Dicer or the formation of secondary structures ( Lin et al., 2021 ). Statistically, there are more than 20,000 known piRNAs in the human genome, which is more than 10 times the number of miRNAs; this suggests that piRNAs may play an important role in gene expression ( Chen et al., 2021b ; Kozomara et al., 2019 ; Kozomara and Griffiths-Jones, 2014 ; Lin et al., 2021 ).…”
Section: Mechanisms Of the Ncrna-mediated Regulation Of Osteogenic Si...mentioning
confidence: 99%
“…PIWI-interacting RNAs (piRNA), are non-coding RNAs (ncRNAs) with a length of 24–32 nucleotides and 2’-O-methylation at their 3’-end, which can play both an agonistic and antagonistic role in the development of cancer ( 165 ). A recent study showed that S1P-S1PR signaling regulated MM survival through upregulation of piR-004800 ( 166 ).…”
Section: Sphingolipid Role In the Hallmarks Associated With MM Progre...mentioning
confidence: 99%